Impact of Attitude, Perceived Ease of Use, Convenience, and Social Benefit on Intention to Use Mobile Payment - Sari, Reza Lidia; Habibi, Ahmad Burhan; Hayuningputri, Ersa Pawitrasari (APMBA (Asia Pacific Management and Business Application), 2022)
The use of mobile payment increases along with technology advancement and the proliferation of mobile payment providers. This study aimed to investigate the effect of perceived ease of use, attitude toward mobile payment, perceived convenience benefit, and social benefit on intention to use mobile payment. A cross-sectional survey was conducted involving 120 mobile payment customers in Surabaya, the 2nd largest city in Indonesia, who used OVO, Go-Pay, LinkAja, or T-cash in the last month and aged no younger than 18 years old. A questionnaire distributed to the participants with accidental sampling technique. A Partial Least Squares (PLS) modeling indicated a positive effect of attitude on intention to use mobile payment among participants. Attitude also fully mediated the links between perceived ease of use, perceived convenience benefit, and intention to use mobile payment. Meanwhile, perceived social benefit was not associated with intention to use mobile payment. Therefore, mobile payment providers should take ease of use and comfort into account when designing their service as they might shape a positive attitude and in turn, increase people’s intention to use the service.